Potential Reduction of Peripheral Local SAR for a Birdcage Body Coil at 3 Tesla Using a Magnetic Shield - van Leeuwen, C.C.; Steensma, B.R.; Glybovski, S.B.; Lunenburg, M.F.J.; Simovski, C.; Klomp, D.W.J.; van den Berg, C.A.T.; Raaijmakers, A.J.E. (Frontiers in physics, 2021)
The birdcage body coil, the standard transmit coil in clinical MRI systems, is typically a shielded coil. The shield avoids interaction with other system components, but Eddy Currents induced in the shield have an opposite direction with respect to the currents in the birdcage coil. Therefore, the fields are partly counteracted by the Eddy currents, and large coil currents are required to reach the desired B 1 + level in the subject. These large currents can create SAR hotspots in body regions close to the coil. Complex periodic structures known as metamaterials enable the realization of a magnetic shield with magnetic rather than electric conductivity. A magnetic shield will have Eddy currents in the same direction as the coil currents. It will allow generating the same B 1 + with lower current amplitude, which is expected to reduce SAR hotspots and improve homogeneity. This work explores the feasibility of a birdcage body coil at 3 T with a magnetic shield. Initially, we investigate the feasibility by designing a scale model of a birdcage coil with an anisotropic implementation of a magnetic shield at 7 T using flattened split ring resonators. It is shown that the magnetic shield destroys the desired resonance mode because of increased coil loading. To enforce the right mode, a design is investigated where each birdcage rung is driven individually. This design is implemented in a custom built birdcage at 7 T, successfully demonstrating the feasibility of the proposed concept. Finally, we investigate the potential improvements of a 3 T birdcage body coil through simulations using an idealized magnetic shield consisting of a perfect magnetic conductor (PMC). The PMC shield is shown to eliminate the peripheral regions of high local SAR, increasing the B 1 + per unit maximum local SAR by 27% in a scenario where tissue is present close to the coil. However, the magnetic shield increases the longitudinal field of view, which reduces the transmit efficiency by 25%.